Analisis Penyerapan Anggaran Belanja Daerah Studi Kasus pada Biro Umum Sekretariat Daerah Provinsi Sulawesi Utara - Hendrik Manossoh; Hendrik Gamaliel; Enolia Novita Muhaling (Syntax Literate, 2023)
The purpose of this study was to find out the mechanisms, constraints in absorbing the budget and efforts to maximize the absorption of the regional budget at the General Bureau of the Regional Secretariat of North Sulawesi Province. This type of research is qualitative research with a case study method. To obtain the necessary data, the authors carried out data collection activities by means of participatory observation, in-depth interviews, and documentation analysis. The results of the study show that the General Bureau has implemented a regional financial management mechanism based on regulations, although there are still some obstacles in its implementation. In addition, as the central unit, it has the function of managing the salaries of benefits for all civil servants who are included in the personnel expenditure category within the Regional Secretariat and has the functional duties of managing Regional Secretariat assets which are included in the capital expenditure category so that it has a fairly large portion of the total budget. However, the realization of the absorption of the budget for the General Bureau in the last 3 years has a sizeable difference between Semesters I and II. Although, the absorption rate is included in the category of moderate budget absorption realization above 90% up to 94.99%. Obstacles faced in absorbing the budget at the General Bureau, namely the urgency of activities and constraints from third parties, availability of budgets and leadership policies, organizational applications/systems and administrative files, human resources and organizational culture (slowback expenditure phenomenon). The efforts made in the absorption of the regional expenditure budget by the General Bureau, namely increasing HR competencies and core values, improving facilities/infrastructure, communication and coordination, supervision and leadership innovation.